Field notes contributed by Babs Padelford and Loren Padelford, summer 1993 - Padelford, Babset al; Padelford, Lorenet al (1993)
Summer report of birds found in western Iowa contributed by Babs Padelford and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1993. Plustek - flatbed